Antioxidative and functional properties of plum oil cake protein isolate prepared by different drying methods - Pantić Jovana R.; Šuput Danijela Z.; Hromiš Nevena M.; Đermanović Branislava B.; Popović Ljiljana M.; Popović Senka Z. (Food and Feed Research)
The global demand for proteins is constantly increasing, resulting in the need for science and industry to explore novel raw materials for protein extraction. Plum oil cake, obtained after plum oil cold pressing, has great potential as a nutritious, low-cost material. The high protein content (up to 50%) of this by-product is ideal for valuable protein-rich ingredients extraction. Protein isolates from plum oil cake (PPI) were prepared using different drying methodsthermal drying (PPIT) and freeze-drying (PPIF). Obtained isolates were compared in terms of their antioxidative properties and techno-functional properties. Protein content and process yield were also examined, resulting in high protein content (over 96%) with no influence of the drying method. The light colour of PPIF would be more appealing to consumers and more suitable for incorporation into food systems. The functional properties of the protein isolates were not significantly affected by different drying methods except for protein solubility. Both PIs exhibited minimum protein solubility at pH 5.0 and maximum solubility at pH 10.0, while PPIF was much more soluble than PPIT. The freeze-drying method led to a much higher antioxidant activity of PPIF. Overall, protein isolates from plum cake obtained from different processing methods differed in appearance, solubility and antioxidant capacity, but yield, protein content and other functional properties were similar. This information will be useful in optimising the production of this protein isolate and benefitting its applications.